Protein Intake in Medical Students, and Its Relationship to Gender and Physical Activity - Dhanty Mukhsina; Ardesy Melizah Kurniati; Mutiara Budi Azhar; Liniyanti D. Oswari; Theodorus Theodorus; Syarinta Adenina (Biomedical Journal of Indonesia, 2022)
Introduction. Protein is a physically and functionally complex macromolecule that has a role in the body. Medical students have been expected to have more knowledge about healthy lifestyles: healthy diet and physical activity. Previous studies have stated many factors affect protein intake. This research was conducted to find out about protein intake and its relationship to gender and physical activity of medical students in the Faculty of Medicine, Universitas Sriwijaya. Methods. This was an analytic observational study with a cross-sectional design. Data were collected using questionnaires, food records and food recall conducted from 8 September 2017 until 27 September 2017, against 279 respondents in the Faculty of Medicine, Universitas Sriwijaya. The data obtained were analyzed with the statistical test of Chi-square with SPSS Version 24. Results. Most of the respondents were female. In this study, the majority of respondents have low physical activity (49.8%). The mean protein intake of the respondents was low (81%). There was no significant relationship between gender and protein intake (p-value=0,135). There was no significant relationship between physical activity and protein intake (p-value=0.299). Conclusion. This study concluded that protein intake was not related to gender and physical activity of medical students